Hereditary Angioedema - A.P. Volokha (Zaslavsky O.Yu., 2014)
Hereditary angioedema - a rare disease caused by a congenital deficiency of C1-inhibitor. Clinical manifestations of the disease - recurrent episodes of angioedema, which manifest in childhood or adolescence, more often localized in the subcutaneous tissue (limbs, face, trunk, genitals) or submucosa (intestine, larynx). Swellings of the larynx are potentially harmful to the patient's life. Early detection enables to carry out timely appropriate treatment and prevention of angioedema. The paper presents a case of hereditary angioedema with manifestation in early childhood. The case study demonstrates the complexity of diagnosis and treatment of hereditary angioedema.